The Turkish Bethylidae (Hymenoptera, Chrysidoidea) fauna, with the new records of Epyrinae and Scleroderminae - Can, İlyas (Zootaxa, 2022)
This study includes the specimens of Epyrinae and Scleroderminae subfamilies belonging to the family of Bethylidae collected from Samsun and Tokat provinces of Turkey between 2006 and 2022. Insect specimens were collected through insect net and hand picking method. At the end of the study, three species belonging to three genera of Epyrinae, Epyris niger Westwood, Gracilepyris rufipes (Say) and Laelius pedatus (Say), and one genus and one species belonging to Scleroderminae, Sclerodermus ephippius Saunders, were determined. This is the first record of the identified species, their genera and subfamilies from Turkey. Brief descriptions of newly recorded species are provided. A preliminary checklist of Turkish Bethylidae (Hymenoptera, Chrysidoidea) is also presented for the first time.